Instilling Hindu Character Values through The Development of E-Comic Based Balinese Satua in Kindergarten - Windayani, Ni Luh Ika; Dewi, Ni Wayan Risna (Universitas Pendidikan Ganesha, 2024)
There are many benefits associated with the usage of e-comics as a medium for developing Hindu character in early childhood. The aim of the research is to develop e-comic based Balinese media to instill Hindu characters in early childhood. The research uses Research and Development (R&D) with a 4D (define, design, develop, disseminate) model. The e-comic based Satua Bali prototype to instill Hindu characters in students was developed through the stages of making a script, characterizing, sketching, digitizing characters, making storyboards and transferring image files to the LibreOffice Impress (PowerPoint) program. Continued to convert the PowerPoint file into a video. Instruments include observation sheets, interviews, as well as validation, practicality and effectiveness sheets. The data analysis technique for validity uses an average score with valid criteria with a score of more than 8.00. The practical aspect uses three criteria; very practical (7-10), practical (4-6) and impractical (1-3). The effectiveness aspect is carried out using the t-test. Validation results from experts and practitioners show that the material aspect is in the valid category. The practicality of e-comic based Satua Bali to instill Hindu character values ​​in students gets practical response results. The results show that there is an influence of implementing e-comic based Satua Bali in instilling Hindu character values ​​in students. Therefore, it can be concluded that e-comic based Balinese Satua media in instilling Hindu characters in early childhood has been well developed and is useful as a learning medium.